A Characterization of Totally Real Carleman Sets and an Application to Products of Stratified Totally Real Sets - Magnusson, Benedikt S.; Wold, Erlend Fornæss (MATHEMATICA SCANDINAVICA, 2016)
We give a characterization of stratified totally real sets that admit Carleman approximation by entire functions. As an application we show that the product of two stratified totally real Carleman sets is a Carleman set.